Modifikasi Media Teknik Dassar Passing Bawah Permainan Bola Voli Melalui Video Tutorial bagi Siswa SD Negeri 190 Tanjung Jabung Barat - Sukamto Sukamto (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2021)
The use of instructional media during the COVID-19 period is expected to make it easier for students to stay enthusiastic about learning at home. Researchers innovate by changing the volleyball that is commonly used for learning in school into a number of simple tools that are more easily found by students.The purpose of this study was to determine the media modification of the basic techniques of passing under volleyball through video tutorials for elementary students, as well as to find out students' understanding through video tutorials of under passing techniques given by the teacher as learning media. This research was conducted in 190 Tanjung Jabung Barat Elementary School, Jambi Province, in the even semester of the 2019/2020 school year.Â By using descriptive qualitative research methods. The subjects in this study were grade 5 students, amounting to 35 students. The results of research conducted by researchers are by uploading video tutorials that have been made to Youtube. Researchers will begin to assess the effectiveness of the video based on input from viewers of the video. In addition, researchers also made a questionnaire / questionnaire containing opinions, and evaluations of videos that have been uploaded. Based on the questionnaire, 54.30% of respondents said the video was effectively used as a learning medium for elementary school students. Keywords : Video Tutorials, Passing Down Penggunaan media pembelajaran di masa COVID-19 diharapkan dapat memudahkan siswa untuk tetap bersemangat belajar di rumah. Peneliti berinovasi dengan mengubah bola voli yang biasa digunakan untuk pembelajaran di sekolah menjadi beberapa alat sederhana yang lebih mudah ditemui oleh siswa. Tujuan penelitian ini adalah untuk mengetahui modifikasi media teknik dasar passing bawah bola voli melalui video tutorial untuk siswa SD, serta untuk mengetahui pemahaman siswa melalui video tutorial teknik passing bawah yang diberikan oleh guru sebagai media belajar. Penelitian ini dilaksanakan di SD Negeri 190 Tanjung Jabung Barat Provinsi Jambi, pada semester genap tahun ajaran 2019/2020.Â Dengan menggunakanÂ metode penelitian deskriptif kualitatif. Subjek pada penelitian ini siswa kelas 5 yang berjumlah 35 siswa. Hasil penelitian yang telah dilakukan oleh peneliti adalah dengan mengunggah video tutorial yang telah dibuat ke Youtube. Peneliti akan mulai menilai tentang keefektifan video berdasarkan dengan masukan dari penonton video tersebut. Selain itu, peneliti juga membuat angket/kuesioner yang berisikan tentang pendapat, dan evaluasi dari video yang sudah diunggah. Berdasarkan angket tersebut, sebanyak 54.30% responden mengatakan video tersebut efektif digunakan sebagai media pembelajaran untuk siswa Sekolah Dasar. Kata kunci: Video Tutorial, Passing Bawah